Management of Arabic Language Competence: Insiders’ Awareness and Experiences/ Manajemen Kompetensi Bahasa Arab: Kedasaran dan Pengalaman Anggota - Lulu Arifah Rahmah; Prayoga Saputra; Nuril Mufidah (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2023)
This research delves into the management of Arabic language competency within the Arabic Program, focusing on its fundamentals and members' experiences. Arabic plays a crucial role in the global context, leading to the emergence of institutions and services for Arabic language learning. Effective competency management becomes key to excellence in mastering the language. The study employs a qualitative approach, exploring both technical aspects and members' experiences. It combines John F. Mee's management theory with psycholinguistics in analyzing Arabic Program learning activities and programs. This research aims to analyze Arabic Language Program Management using John F. Mee's model in managing the language competency of organizations or study groups. Key findings include activity planning, organizational structure, motivation, and direct supervision. Additionally, the research highlights challenges such as variations in members' initial understanding and the need for diverse learning approaches. The practical implications involve developing more effective Arabic language competency management strategies by participating in many competition activities from various division branches, Arabic language training programs, and workshops, benefiting members by motivation, and increasing the competitiveness of organizations or learning groups globally through providing rewards to members published via social media platforms. This research contributes to the literature on competency management and Arabic language learning.Abstrak: Penelitian ini mendalami pengelolaan kompetensi bahasa Arab dalam Program Bahasa Arab, dengan fokus pada fundamental dan pengalaman anggota. Bahasa Arab memainkan peran penting dalam konteks global, yang menyebabkan munculnya institusi dan layanan pembelajaran bahasa Arab. Manajemen kompetensi yang efektif menjadi kunci keunggulan dalam penguasaan bahasa. Penelitian ini menggunakan pendekatan kualitatif, mengeksplorasi aspek teknis dan pengalaman anggota. Menggabungkan teori manajemen John F. Mee dengan psikolinguistik dalam menganalisis kegiatan dan program pembelajaran Bahasa Arab. Penelitian ini bertujuan untuk menganalisis Manajemen Program Bahasa Arab dengan model John F. Mee dalam pengelolaan kompetensi bahasa organisasi atau kelompok belajar. Temuan utama meliputi perencanaan kegiatan, struktur organisasi, motivasi, dan pengawasan langsung. Selain itu, penelitian ini menyoroti tantangan seperti variasi dalam pemahaman awal anggota dan perlunya pendekatan pembelajaran yang beragam. Implikasi praktisnya meliputi pengembangan strategi manajemen kompetensi bahasa Arab yang lebih efektif dengan mengikuti banyak kegiatan lomba dari berbagai cabang devisi, program latihan dan workshop bahasa arab, memberikan manfaat bagi anggota berupa motivasi, dan meningkatkan daya saing organisasi atau kelompok pembelajaran secara global melalui pemberian reward kepada anggota yang dipublikasikan melalui platfrom media sosial. Penelitian ini memberikan kontribusi terhadap literatur manajemen kompetensi dan pembelajaran bahasa Arab.